Pelatihan Desain Media Pembelajaran Inovatif Berbasis Platform Canva bagi Guru SMP Negeri 1 Depapre Kabupaten Jayapura - Sembiring, Desy Anita Karolina; Risamasu, Putri Ellen Gracia; Tijow, Meylani Aljeinie; Aryesam, Agnes; Sogalrey, Febi Adriana Mutiara; Karim, Abdul; Selfe, Selvianus; Rosiyanti, Rosiyanti; Rafra, Joshua Alexander (Jurnal Pengabdian UNDIKMA, 2024)
This service aims to enhance teachers’ knowledge and skills in designing innovative learning using the Canva platform as an engaging teaching tool. The method employed in conducting this service was training based on participatory approaches and individual communication. The partners in this service were 35 teachers from SMP Negeri 1 Depapre, Jayapura Regency. The results of this service showed that the teachers possessed knowledge and skills in operating the Canva application.Â ItÂ was evidenced by the outcomes of activities such as designing learning media such as student ID cards or creating math problems using Canva. Throughout the training, there was a high level of enthusiasm from the school staff in learning the Canva platform for teaching purposes relevant to their subject areas.Â It is hoped that inÂ the future, teachers will continue to develop their abilities in applying Canva to aid in the preparation of teaching materials.